'Justin Bieber Sounds Girlie': Young People's Celebrity Talk and Contemporary Masculinities. (August 2015) - Allen, Kim; Harvey, Laura; Mendick, Heather
In this article, we explore the ways that contemporary young masculinities are performed and regulated through young people's relationship with celebrity. We address the relative paucity of work on young men's engagements with popular culture. Drawing on qualitative data from group interviews with 148 young people (aged 14-17) in England, we identify 'celebrity talk' as a site in which gender identities are governed, negotiated and resisted. Specifically we argue that celebrity as a space of imagination can bring to the study of masculinities a focus on their affective and collective mobilisation. Unpicking young men's and women's talk about Canadian pop star Justin Bieber and British boyband One Direction, we show how disgust and humour operate as discursive-affective practices which open up and close down certain meanings and identities. We conclude that while there have been shifts in the ways that masculinities are performed and regulated, hierarchies of masculinities anchored through hegemonic masculinity remain significant.